Preparation and Characterization of Potato Peel Starch-Based Bioplastic Using Different Starch and Gelatin Concentrations - Sarah Nur Amanah; Rachmah Nanda Kartika; Yoga Putra Pratama (Indonesian Journal of Mathematics and Natural Sciences, 2026)
Conventional plastic packaging has contributed significantly to environmental pollution due to its non-biodegradable nature. One promising alternative is potato peel starch-based bioplastic, which utilizes agricultural waste as a renewable raw material for biodegradable packaging. This study aimed to produce and characterize potato peel starch-based bioplastic with different starch and gelatin concentrations by evaluating its thickness, water absorption, solubility, and moisture content. Bioplastics were prepared using the solution casting method with starch concentrations of 3, 5, and 7 g and gelatin concentrations of 0, 0.5, and 1 g. Other materials used included glycerol as a plasticizer, chitosan, acetic acid, distilled water, and peppermint oil. The resulting bioplastics were characterized by measuring thickness, water absorption, solubility, and moisture content. The results showed that the bioplastics had thickness values ranging from 0.182 to 0.542 mm, water absorption of 52.37-82.15%, solubility of 23.68-39.84%, and moisture content of 13.94-18.92%. In general, increasing the concentrations of starch and gelatin tended to reduce water absorption, solubility, and moisture content, indicating the formation of a denser and more stable polymer matrix. The P7G1 formulation (7 g starch and 1 g gelatin) exhibited the most favorable characteristics, with the lowest water absorption, solubility, and moisture content. Therefore, this formulation has the potential to be further developed as an environmentally friendly bioplastic packaging material